Observations of Marine Birds and Mammals Wintering at Polynyas and Ice Edges in the Belcher Islands, Nunavut, Canada - Gilchrist, H. Grant; Robertson, Gregory J. (ARCTIC, 2000)
In the Belcher Islands, southeast Hudson Bay, Canada, two types of open water exist during winter: 1) large, wind-driven expanses of water along landfast ice edges and 2) recurring polynyas located between small islands (most <10 ha and <15 m deep). In severe winters, only polynyas persist. In March 1998 and 1999, we recorded the species and numbers of birds and marine mammals present at ten polynyas and along four landfast ice edges around the Belcher Islands. To help interpret our observations, we also collected traditional ecological knowledge from local Inuit. Large flocks of common eiders Somateria mollissima (200-12500 birds) were seen along floe edges, and small groups occurred in some polynyas. King eiders S. spectabilis were also observed at several locations, always associated with common eiders. Oldsquaw ducks Clangula hyemalis were common (flocks of 100-500 birds) and occurred primarily at polynyas. Our observations of king eiders represent a significant northern range expansion for this species in Canada during winter. Ravens Corvus corax and snowy owls Nyctea scandiaca were observed along landfast ice edges. Ravens were feeding on the remains of seals killed by Inuit hunters and polar bears Ursus maritimus, and owls apparently hunted sea ducks that were loitering on ice edges at night. We regularly observed bearded seals Erignathus barbatus and ringed seals Phoca hispida at polynyas and floe edges. One beluga whale Delphinapterus leucas was observed by our Inuit guides along a western landfast ice edge, and three walrus Odobenus rosmarus were observed at a floe edge along the southern margin of the Belcher Islands. Clearly, the small recurring polynyas and ice floe edges around the Belcher Islands are important wintering habitat for oldsquaw and common and king eider ducks. L'hiver, dans les îles Belcher, au sud-est de la baie d'Hudson (Canada), l'eau libre est présente sous deux formes: 1) de vastes étendues d'eau créées par le vent, longeant la lisière de la glace de rive et 2), des ...